PHILOSOPHICAL REFLECTIONS UPON MODERN AESTHETIC PROCESSES - Скальська, Д. М.; Скальська, М. Л. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The newest philosophical and aesthetic perspectives going back to structuralism and spreading to postmodernism account for logical realization of the processes accompanied the dynamic transition and co-existence of Modernity Era (modern times) and Post Modernity Era (post modern times). They reflect both particular forms of anthropological perception of the world and the situation defined as a state of post anthropological perspectives.